Water sky - George, Jean Craighead, 1919-2012. ([New York] : HarperTrophy, 1989)
A boy who goes to Barrow, Alaska, to live with friends of his father for awhile learns the importance of whaling to the Eskimo culture.
GR 6-8
Accelerated Reader AR
Reading Counts RC
Keywords: Whaling -- Juvenile fiction; Eskimos -- Juvenile fiction; Indians of North America -- Juvenile fiction